Atom probe crystallography: characterization of grain boundary orientation relationships in nanocrystalline aluminium. - Moody, M; Tang, F; Gault, B; Ringer, S; Cairney, J (2011)
Spatial Distribution Maps (SDM) in their various forms have previously been used to identify and characterize crystallographic structure within APT reconstructions. Importantly, it has been shown that such SDM analyses can also provide the crystallographic orientation of the specimen with respect to the direction of the detector in the original experiment. In this study, we investigate the application of SDMs to the analysis of APT reconstruction of a nanocrystalline Al film. We demonstrate that significant intra-granular crystallographic information is retained in the reconstruction, even in the x-y plane perpendicular to the direction of the detector. Further, the crystallographic orientation of the grains can be characterized highly accurately not only with respect to the bulk specimen but also their misorientation with respect to neighbouring grains.